Plan de marketing estratégico para la empresa agropecuarios Cayambe en el cantón Joya de los Sachas, provincia de Orellana, para el periodo 2017 - 2021 - Cambo Caiza, Lida Leonor (2017)
This work is the main general objective: "Make a strategic marketing plan for the company" agricultural CAYAMBE "in the canton of Joya de the Sachas, Orellana province, for the period 2017-2021", for this purpose was used the respective methods such as: the inductive, deductive, analytical and bibliographic; and them techniques of observation direct, interview to the Manager and survey both to them 9 employees and to those customers in a shows of 338 customers. The study is started with the analysis situational, in which are addressed both the environment internal as external. In the environment internal is analyzed factors as the political, economic, social, technological and them five forces of PORTER, in where in the matrix EFE the company reached a rating of 2,77 result that indicates some advantage in its average external. For the analysis of the internal environment was the collection of information through research techniques; it is thus that interviewed the Manager of the company, are also surveyed employees and customers. With the information gathered was the construction of the EFI Matriz, this matrix the company obtained a weighted score of 2.65 which means that there is predominance of strengths over weaknesses in the company? Subsequently is proceeded to the development of the matrix SWOT, in the crossing of them variables were 4 objectives strategic, which is broken down in the proposed. Finally the budget required for the execution of the plan operating POA is of $30.953, 20; it is estimated that such investment will allow strengthening the image of the company in the market and thus improve their profitability.